2016
DOI: 10.1016/j.jval.2016.09.1326
|View full text |Cite
|
Sign up to set email alerts
|

Network Meta-Analysis To Evaluate The Efficacy of Ixekizumab In The Treatment of Moderate-To-Severe Psoriasis

Abstract: Objectives: Graft-versus-host disease (GVHD) is a severe complication of allogenic stem cell transplantation. Preliminary data suggest the potential role of ruxolitinib as a new treatment option in patients with corticosteroid-refractory GVHD. The aim of the present study was to explore the effectiveness and safety of ruxolitinib as a salvage therapy in this population. MethOds: A single-center, retrospective, observational study was carried out. Inclusion criteria: all patients with corticosteroidrefractory G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…For the previously reported SLR (data collected from January 1990 to November 2015, with an update from November 2015 to November 2016) the following databases were searched in Ovid: Embase, Ovid MEDLINE, Ovid MEDLINE Daily Update, Ovid MEDLINE In‐Process & Other Non‐Indexed Citations, PsycINFO, Econlit, ACP Journal Club, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Cochrane Methodology Register, Database of Abstracts of Reviews of Effects, Health Technology Assessment, NHS Economic Evaluation Database and Database of Abstracts of Reviews of Effects. This analysis was carried out for previously reported NMAs; of the seven secukinumab studies identified, five met the criteria for selection in this MAIC.…”
Section: Methodsmentioning
confidence: 81%
See 3 more Smart Citations
“…For the previously reported SLR (data collected from January 1990 to November 2015, with an update from November 2015 to November 2016) the following databases were searched in Ovid: Embase, Ovid MEDLINE, Ovid MEDLINE Daily Update, Ovid MEDLINE In‐Process & Other Non‐Indexed Citations, PsycINFO, Econlit, ACP Journal Club, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Cochrane Methodology Register, Database of Abstracts of Reviews of Effects, Health Technology Assessment, NHS Economic Evaluation Database and Database of Abstracts of Reviews of Effects. This analysis was carried out for previously reported NMAs; of the seven secukinumab studies identified, five met the criteria for selection in this MAIC.…”
Section: Methodsmentioning
confidence: 81%
“…The systematic literature review (SLR) was performed in line with recommended guidelines from the Cochrane Handbook of Systematic Reviews of Interventions. 15 For the previously reported SLR (data collected from January 1990 to November 2015, with an update from November 2015 to November 2016) 10…”
Section: Systematic Literature Review For Previous Network Metaanalysesmentioning
confidence: 99%
See 2 more Smart Citations
“…8 The technique borrows strength from indirect evidence to enable the simultaneous evaluation of relative effects that have not been investigated directly in RCTs 9 and has been used extensively to evaluate short-term effects of psoriasis treatments. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The objective of this study was to compare novel systemic therapies, both biologic and non-biologic, approved for the treatment of moderate-to-severe psoriasis by conducting a SLR and NMA of Psoriasis Area and Severity Index (PASI) outcomes measured at or around 1 year.…”
Section: Introductionmentioning
confidence: 99%